Comparison of Health-related Quality of Life Between Double-door Laminoplasty and Selective Laminoplasty for Degenerative Cervical Myelopathy, With a Minimum Follow-up of 5 Years. Issue 4 (15th February 2019) - Hirota, Ryosuke; Miyakoshi, Naohisa; Yoshimoto, Mitsunori; Hongo, Michio; Hamada, Shuto; Kasukawa, Yuji; Oshigiri, Tsutomu; Ishikawa, Yoshinori; Iesato, Noriyuki; Kudo, Daisuke; Tanimoto, Katsumasa; Terashima, Yoshinori; et al.
Abstract : Study Design: A retrospective analysis of prospectively collected multicenter observational data. Objective: The aim of this study was to compare the health-related quality of life (HR-QOL) of double-door laminoplasty (DDL) and selective laminoplasty (SL) in patients with degenerative cervical myelopathy (DCM) in two institutions, with a minimum follow-up of 5 years. Summary of Background Data: No study has compared DDL and SL regarding postoperative HR-QOL with a follow-up of more than 5 years. Methods: One-hundred ninety patients who underwent DDL (n = 77) or SL (n = 113) participated in this study. Short-form 36 (SF-36), Japanese Orthopedic Association Cervical Myelopathy Evaluation Questionnaire (JOACMEQ), Neck Disability Index (NDI), and visual analog scale (VAS) values were compared between the groups. Results: Thirty-seven DDL and 52 SL patients were evaluated. The mean follow-up period was 8 years and the follow-up rate was 46.8%. No significant differences were found regarding age and JOA score at baseline. At the follow-up, there were no significant differences in SF-36, JOACMEQ, and VAS score, while the NDI score for headache and sleeping were higher in the SL group. After dividing the SL group into short and long SL subgroups, the long SL subgroup showed a significantly lower score in bodily pain in SF-36, lower and bladder function in JOACMEQ, and pain intensity, personal care, headaches, and sleeping in NDI compared with the other groups. Conclusion: No significant differences were found in SF-36, JOA score, and NDI, except for the NDI subscale of headache and sleeping. The subgroup analysis showed that the long SL group showed a decreased QOL compared with the short SL and DDL groups. Level of Evidence: 3 Abstract : Midterm clinical results were compared between double-door laminoplasty and selective laminoplasty in patients with degenerative cervical myelopathy. Postoperative Short-form 36, Japanese Orthopedic Association Cervical Myelopathy Evaluation Questionnaire, Neck Disability Index, and visual analog scale were nearly equivalent in both groups. Patients who underwent long selective laminoplasty tended to have poorer results.